A study of impact force on modern soccer balls - Koizumi, A.; Hong, S.; Sakamoto, K.; Sasaki, R.; Asai, T. (Procedia Engineering, 2014)
Soccer balls differing in surface material and number of panels were analysed, and a kick-robot equipped with a dynamometer was used to measure the impulsive force at the time of impact. Cafusa had the smallest maximum impulsive force, whereas Jabulani had a larger impulse than all other balls at each tested speed. These results presumably relate to the flexibility of the surface material and structural characteristics of each ball. One reason why Jabulani has the highest impulse may be that the machine-stitched composition of its inner layer is stiffer than the strips of cloth stuck together in Cafusa.